Magnetic Activities of Wolf 359: Starspot Distribution and Quasiperiodic Pulsation Using TESS Data - Diya Ram; Soumen Mondal; Samrat Ghosh; Rajib Kumbhakar (The Astrophysical Journal, 2025)
Wolf 359 is the fifth closest (∼2.4 pc) star to Earth and a candidate exoplanet-hosting M6 dwarf. We studied the distribution of starspots and flaring activities of Wolf 359 to understand its stellar atmosphere and magnetic activities. Using 2 minute short-cadence Transiting Exoplanet Survey Satellite (TESS) data on this highly active star, we found 48, 46, and 32 flares in Sectors 45, 46, and 72, respectively. The rotation period from TESS is estimated to be 2.69 days with negligible error, which matches well with the previous literature values. We estimated the bolometric flare energy in the range of 10 ^30 –10 ^32 erg, including a high flare event of 4.2 ± 0.5 × 10 ^32 erg with a duration of 244.8 minutes. A high magnetic field strength of 0.18 kG is required to produce such a high flare. Interestingly, we first detect two complex flare events with oscillation periods of 104.56 ± 0.59 minutes and 39.22 ± 0.42 minutes in Sectors 45 and 46, probably caused by periodic motions of the emitting plasma or oscillatory reconnection. We estimated the mean spot temperature to be 2772 ± 100 K and the spot area to be 1.30% of the area of the star. We also correlate the duration of a flare event with its energy, $\bigtriangleup t\propto {E}_{bol}^{0.55± 0.01}$ , and this steeper slope likely reflects differences in magnetic field topology, atmospheric cooling behavior, and possibly multi-loop flare complexity compared to other M dwarfs. We noticed the deviation in flare rate distribution and orbital phases, indicating the presence of highly active regions, or it might be a star–planet interaction.